(untitled) (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2014)
تناول هذا البحث دراسة تأثير نسبة المزج (ماء - كحول) في تحديد الزرنيخ بطريقة المعايرة الكمونية الآلية , باستخدام كحول (ميتانول _ إيتانول _ بروبانول)، أجريت عملية المعايرة لحجم محدّد من المحلول المدروس بحجم محدد من محلول قياسي من اليود باستخدام جهاز المعايرة الكمونية الآلية , وذلك بعد تطبيق الشروط (التحليلية والتقنية)المثلى لتحديد الزرنيخ ، ومن ثمّ قمنا بدراسة تأثير نسب المزج في حدّ الكشف عن الزرنيخ في الأوساط المختلطة (ماء_ كحول) . أظهرت الدراسة أن قيمة حد الكشف للزرنيخ تتغير بتغير نوع الكحول المستخدم و نسبته في وسط التفاعل، إذ وصلت إلى (M 10-7× (1وذلك في وسط (75:25 ماء_ ميتانول) ، وعند استخدام وسط (75:25 ماء_ ايتانول) وصل حدّ الكشف إلى (M 10-4× (1، وبالنسبة للبروبانول وصل حد الكشف إلى (M 10-3× (1. كما وصلت قيمة حدّ الكشف للزرنيخ إلى (M 10-5× (1, وذلك في وسط (50:50 ماء_ ميتانول) ، أمّا عند استخدام وسط (50:50 ماء_ ايتانول) وصل حد الكشف إلى (M 10-3× (1، أما بالنسبة للبروبانول وصل حدّ الكشف إلى (M 10-2× (1. بينت الدراسة أنّ استخدام النسبة (75:25 ماء_ كحول) أعطت قيمة أقل لحد الكشف , وبالتالي نتائج أفضل. كما تم حساب الانحراف المعياري و الانحراف المعياري المئوي وحدّ الثقة , بالإضافة إلى الإسترجاعية التي دلّت على كفاءة الطريقة في تحديد تركيز الزرنيخ وحدّ الكشف لكل وسط . This research study the effect of the proportion of the media (water - alcohol ) to determine where the arsenic used alcohol ( methanol _ ethanol _ propanol ) Using a Potentiometric method. It conducted the calibration process for the specific size of the solution studied a specific size of the standard solution of iodine Using a Potentiometric method , after the application of analytical conditions and technical optimal to determine arsenic , and then we studied the effect of mixing ratio on the detection limit for arsenic in mixed media (water _ Alcohol ) . The study showed that the value of the detection limit of arsenic vary with the type of alcohol used and accounted for in the reaction medium , it reached to (1× 10-7 M) in media (75:25 water _ methanol ) , but when you use a media ( 75:25 water _ ethanol ) arrived to the limit of detection (1×10-4 M ), As for propanol arrived to the limit of detection (1×10-3 M). where the value reached detection limit of arsenic to (1× 10-5 M) in media ( 50:50 water _ methanol ) , but when you use a media ( 50:50 water _ ethanol ) arrived to the limit of detection (1×10-3 M ), As for propanol arrived to the limit of detection (1×10-2 M). The study showed that the use of the ratio ( 75:25 water _ alcohol ) gave a higher value limit of detection and therefore better results . Was calculated as the standard deviation and standard deviation percentile confidence limit in addition to the feedback that indicates the efficiency of the method of determining the concentration of arsenic detection limit for each medium.